Transformation of Kakawin Bharatayudha Into The Story of Pandawa Lima - Cika, I Wayan; Soreyana, I Made; Teguh, I Wayan (Udayana Journal of Social Sciences and Humanities; Vol 1 No 2 (2017): UJoSSH, September 2017, 2017)
The story of Pandawa Lima ‘Hikayat Pandawa Lima’ (abbreviated to HPL) written in Malay is a literary work transformed from the Mahabharata Epic ‘Wiracarita Mahabharata,’ especially ‘Kakawin Bharatayuda’ (abbreviated to KBY) written in the Old Javanese language. As a transformational literary work, additions, and reductions could not be avoided. The part that was added and reduced depended on the adapter’s way of thinking and socio-culture values. It was also closely related to the linguistic, literary and cultural conventions inspiring the transformational process. This present study is intended to discuss how the adapter received KBY as the source text (hypogram), what adjustments were made, and how they were made. The problems of the study were analyzed using the theory of literary reception and the qualitative and hermeneutic method. The objective of the study is to reveal the HPL adapter’s reception of its source text (hypogram). The result of the analysis shows that the HPL adapter adapted KBY without degrading the hypogram, meaning that the great values which the hypogram contains are still intact and complete. However, several adjustments were made in HPL; they are the incidents, names of weapons, and characters.